The Technological Literacy Profile of Physics Education Students in Utilizing Digital Applications To Support Quality Education - Frendi Ihwan Syamsudin; Ketang Wiyono; Evelina Astra Patriot; Azlan Kamari (Berkala Ilmiah Pendidikan Fisika, 2026)
Technological literacy has become one of the essential competencies for university students in the digital era, particularly in supporting the achievement of Sustainable Development Goal (SDG) 4 on quality education. This study aims to analyze the technological literacy profile of physics education students at Universitas Sriwijaya in utilizing digital devices and applications for learning purposes. Data were collected through interviews with 30 respondents. The dimensions in the interview instrument included technology access, technology understanding, and technology production. The data were analyzed qualitatively using coding analysis with the Quirkos application. The findings reveal that students predominantly rely on smartphones and laptops to support learning activities, although unstable network quality remains a significant obstacle. Students’ experiences in utilizing digital learning media and accessing scientific journals are still relatively limited. Various digital applications, such as Google Drive, PhET Colorado, Microsoft Word, Canva, and CapCut, are commonly used to facilitate learning. Technological literacy is supported by the availability of internet access, conducive learning environments, and campus facility support, yet it is hindered by limited technological understanding, data security risks, network instability, and the persistence of plagiarism practices. The findings imply that enhancing technological literacy is crucial for preparing students to engage in innovative and ethical digital learning environments. Therefore, universities should integrate digital literacy programs through educational technology training, project-based learning, and the habituation of digital ethics to foster adaptive and sustainable physics learning